Training creative cognition: adolescence as a flexible period for improving creativity - Stevenson, Claire E.; Kleibeuker, Sietske W.; de Dreu, Carsten K. W.; Crone, Eveline A. (Frontiers in Human Neuroscience, 2014)
Creativity commonly refers to the ability to generate ideas, solutions, or insights that are novel yet feasible. The ability to generate creative ideas appears to develop and change from childhood to adulthood. Prior research, although inconsistent, generally indicates that adults perform better than adolescents on the alternative uses task, a commonly used index of creative ideation. The focus of this study was whether performance could be improved by practicing alternative uses generation. We examined the effectiveness of creative ideation training in adolescents (13-16 yrs., N=71) and adults (23-30 yrs., N=61). Participants followed one of three types of training, each comprising 8 twenty-minute practice sessions within two weeks time: 1) alternative uses generation (experimental condition: creative ideation); 2) object characteristic generation (control condition: general ideation); 3) rule-switching (control condition: rule-switching). Progression in fluency, flexibility, originality of creative ideation was compared between age-groups and training conditions. Participants improved in creative ideation and cognitive flexibility, but not in general ideation. Participants in all three training conditions became better in fluency and originality on the alternative uses task. With regard to originality, adolescents benefitted more from training than adults, although this was not specific for the creative ideation training condition. These results are interpreted in relation to a) the different underlying processes targeted in the three conditions and b) developmental differences in brain plasticity with increased sensitivity to training in adolescents. In sum, the results show that improvement can be made in creative ideation and supports the hypothesis that adolescence is a developmental stage of increased flexibility optimized for learning and explorative behavior.